Ultralearning : master hard skills, outsmart the competition, and accelerate your career - Young, Scott H. (Harper Business, an imprint of HarperCollinsPublishers, 2019)
Learn a new talent, stay relevant, reinvent yourself, and adapt to whatever the workplace throws your way. Ultralearning offers nine principles to master hard skills quickly. This is the essential guide to future-proof your career and maximize your competitive advantage through self-education. Young documents the methods he and others have used and shows that, far from being an obscure skill limited to aggressive autodidacts, ultralearning is a powerful tool anyone can use to improve their career, studies, and life.